2014
DOI: 10.1093/cid/ciu834
|View full text |Cite
|
Sign up to set email alerts
|

Significant Reduction in HIV Virologic Failure During a 15-Year Period in a Setting With Free Healthcare Access

Abstract: The proportion of HIV-infected patients experiencing VF during routine care fell markedly between 1997 and 2009-2011, to only 9.7%. This was attributed to the advent of fully active and better-tolerated antiretroviral drugs, and to national guidelines recommending rapid management of VF after mid-2000.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
18
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 44 publications
6
18
0
1
Order By: Relevance
“…In agreement with other studies, we found that older age15, 16 and later calendar year13, 20 at start of ART were associated with a reduced risk of viral rebound. Older age is associated with better adherence,21, 22 which could explain the reduced rate of rebound in older people in our study.…”
Section: Discussionsupporting
confidence: 93%
“…In agreement with other studies, we found that older age15, 16 and later calendar year13, 20 at start of ART were associated with a reduced risk of viral rebound. Older age is associated with better adherence,21, 22 which could explain the reduced rate of rebound in older people in our study.…”
Section: Discussionsupporting
confidence: 93%
“…27 To build on the near universal reach of community-based HIV testing, decentralized ART delivery services have the potential to overcome bottlenecks in care at overburdened clinics. 28 Current ART regimens are often once-daily, safe and well-tolerated, 29 thus, moving ART initiation and refill supply into the community, in addition to testing, would overcome barriers to care for HIV-positive persons who do not need clinic services. 19 To reach the UNAIDS goal of 73% of HIV-positive persons virally suppressed 11 and 80% of HIV-negative men accessing male circumcision, 9 requires highly effective combination HIV prevention.…”
Section: Discussionmentioning
confidence: 99%
“…Virologic failure was also associated with initiating treatment in earlier calendar years, which is consistent with trends seen in other studies. 24,26,27 Improvements in efficacy and tolerability of antiretroviral agents, changes in clinical care such as increased clinician experience, and other unmeasured variables may be contributing to this trend. In contrast, incidence of major regimen change increased over time.…”
Section: Discussionmentioning
confidence: 99%